Greater avoidance behavior in individuals with posttraumatic stress disorder symptoms. (4th May 2017) - Sheynin, Jony; Shind, Christine; Radell, Milen; Ebanks-Williams, Yasheca; Gilbertson, Mark W.; Beck, Kevin D.; Myers, Catherine E.
Abstract: While avoidance is a core symptom of PTSD, little is known about whether individuals with PTSD show a general cognitive bias to acquire and express avoidance, in situations not related to trauma or fear. Here, we used a computer-based task to examine operant acquisition and extinction of avoidance in participants with and without severe self-reported PTSD symptoms. A total of 119 participants (77 male, 42 female; 74 veteran, 45 civilian) with symptoms (PTSS; n  = 63) or with few/no symptoms (noPTSS; n  = 56) performed a task, in which they controlled a spaceship and could shoot a target to gain points or hide in "safe areas" to escape or avoid on-screen aversive events. Results show that participants with PTSS exhibited more avoidance across trials than noPTSS participants, particularly due to more avoidance behavior in PTSS females compared to noPTSS females. Avoidance behavior decreased across extinction trials but interactions with PTSS and gender fell short of significance. Overall, PTSD symptoms were associated with propensity to acquire and express avoidance behavior, in both civilians and veterans, and even in a cognitive task that does not explicitly involve trauma or fear. This effect was more pronounced in females, highlighting the role of gender differences in PTSD symptomatology. Importantly, this study also demonstrates the potential of an objective assessment of avoidance behavior, which could be used to supplement the common but limited self-report tools.